2010
DOI: 10.1016/j.joep.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Distance matters in away games: Evidence from the German football league

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…The following data sources are used to complement the data set of Oberhofer et al (2010): Information on relegation and promotion is taken from the online sources http://www.f-archiv.de and http://t-online.sport-dienst.de/vereine/; financial figures are obtained from Welt am Sonntag and http://t-online.sport-dienst.de; city size numbers for 2006 have been gathered from Statistisches Bundesamt Deutschland (http://www.destatis.de); and the clubs' year of foundation is published in Gruene and Karn (2009) and at www.bundesliga.de.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The following data sources are used to complement the data set of Oberhofer et al (2010): Information on relegation and promotion is taken from the online sources http://www.f-archiv.de and http://t-online.sport-dienst.de/vereine/; financial figures are obtained from Welt am Sonntag and http://t-online.sport-dienst.de; city size numbers for 2006 have been gathered from Statistisches Bundesamt Deutschland (http://www.destatis.de); and the clubs' year of foundation is published in Gruene and Karn (2009) and at www.bundesliga.de.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Previous research found that an increase in distance increases in the likelihood that a team is defeated. 17 As a result, we expect the opposite for games that occur between teams in close proximity to each other. Thus, we hypothesize: H8: Playing in a derby match has a positive effect on match outcome.…”
Section: Introductionmentioning
confidence: 96%
“…However, this phenomenon has been studied most widely in soccer. Numerous research has centred around analysing the home advantage in soccer matches at the national level, moving from country-specific studies in Australia (Goumas, 2014a), Brazil (Pollard et al, 2008), England (Clarke and Norman, 1995;Nevill et al, 1996;Carmichael and Thomas, 2005), Germany (Oberhofer et al, 2010), Greece (Armatas and Pollard, 2012), Spain (Sánchez et al, 2009;Saavedra et al, 2015), and Turkey (Seckin and Pollard, 2008), among others, to cross-country investigations (Pollard, 2006a(Pollard, , 2006bPollard and Gómez, 2014;Leite and Pollard, 2018). Additionally, research on the home advantage in soccer has been conducted based on World Cup data (Torgler, 2004;, international club competitions data (Page and Page, 2007;Poulter, 2009;Goumas, 2013Goumas, , 2014b, and data on international football games played in South America (McSharry, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several of the aforementioned studies have investigated the moderators of the home advantage in soccer. Among the most discussed factors influencing this home advantage are: (i) crowd effects (Nevill et al, 1996;Pollard and Pollard, 2005a;Sánchez et al, 2009;Oberhofer et al, 2010;Goumas, 2013;Ponzo and Scoppa, 2018;; (ii) referee bias (Nevill et al, 1996;Sutter & Kocher, 2004;Nevill et al, 2013); (iii) territoriality effects (Neave and Wolfson, 2003;Pollard, 2006aPollard, , 2006bPollard et al, 2008;Seckin and Pollard, 2008;Armatas and Pollard, 2012;Gómez, 2013, 2014;; (iv) travel effects (Clarke and Norman, 1995;McSharry, 2007;Pollard et al, 2008;Oberhofer et al, 2010;Armatas and Pollard, 2012;Bäker et al, 2012;Goumas, 2014aGoumas, , 2014b; and (v) familiarity effects (Pollard, 2002;Watson and Krantz, 2003;2014;.…”
Section: Introductionmentioning
confidence: 99%